Green human resource management (GHRM) practices and organizational citizenship behaviour for environment (OCBE): a case of fertilizer company in Kedah - Mohd Faizal, Mohd Rofi (2019)
Environmental issues created by industries are a concern to local communities, governments and related agencies. It will raise serious concerns about the environment and the level of operation of the industry. This situation calls for the contribution of business organizations as employees to address environmental issues. This study examined factors that are the correlate with organizational citizenship behaviour environment (OCBE) at industries organizations in Malaysia. The purpose of this research is to examine the correlation between Green Human Resources Management (GHRM) practices and Organizational Citizenship Behavior for Environmental (OCBE) at NPK Fertilizer Company. OCBE among employees can contribute to environmental management of organization. The role of green HRM practice is a one of organization strategy in shaping OCBE among employee. This study assessed the correlation between seven dimension of GHRM practices, namely green job analysis and design, green recruitment and selection, green training and development, green performance management, green compensation management, green health and safety and green labor relation and involvement with OCBE. The research was conducted in fertilizer company in Kedah and 145 respondents have participated in this survey. This research used survey methodology by questionnaire, then analysed by descriptive analysis, factor analysis, reliability test and correlation analysis using statistical package for social sciences (SPSS). Findings showed that green job analysis and design having the moderate significant positive relationship with OCBE. The study also found that other six dimension of GHRM which green recruitment and selection, green training and development, green performance management, green compensation management, green health and safety and green labor relation and involvement have a low significant positive relationship with OCBE. Finally, discussion and conclusion on the implication for this research were presented.